2007
DOI: 10.1021/cm070963y
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Site Preference of Ba-Doped α-Tricalcium Phosphate (Ca1-xBax)3(PO4)2through High-Resolution Synchrotron Powder Diffraction (x= 0.05 to 0.15)

Abstract: The single phase of barium-substituted alpha tricalcium phosphate (Ba-α-TCP) (Ca1- x Ba x )3(PO4)2 (x = 0.05, 0.10, and 0.15) has been prepared by solid-state reactions. The crystal structure of the Ba-α-TCP powders has been investigated by high-resolution synchrotron powder diffraction and the Rietveld method. Diffraction data were successfully analyzed by the single phase Ba-α-TCP (space group P21/a). Unit-cell parameters a, b, c, and β increase with increasing Ba content. Most of the Ba atoms are located a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…This suggested that the BVS values in undoped system could be used as an indicator for the site preference of dopant cations: the dopant cations with relatively large ionic radius prefer to sites with smaller BVS values; while small dopant cations preferentially occupy crystallographic sites with larger BVS values. This correlation of the site preference of doping atom and BVS values is similar to that reported by Yashima and Kawaike [32]. It should be noted that the case of Bi 3+ substitution on La 3+ is not consistent with this regulation.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This suggested that the BVS values in undoped system could be used as an indicator for the site preference of dopant cations: the dopant cations with relatively large ionic radius prefer to sites with smaller BVS values; while small dopant cations preferentially occupy crystallographic sites with larger BVS values. This correlation of the site preference of doping atom and BVS values is similar to that reported by Yashima and Kawaike [32]. It should be noted that the case of Bi 3+ substitution on La 3+ is not consistent with this regulation.…”
Section: Resultssupporting
confidence: 88%
“…Hence they are usually used to explain some perplexing problem of stability of structure. For example, Harrington [32]. Our third goal of this paper is to validate the correlation of the site preference of doping atom and BVS in β-La 2 Mo 2 O 9 based on first principle results.…”
Section: Introductionmentioning
confidence: 99%
“…However, the evolution of the XRD patterns corresponds to the internal structural changes of α-TCP, but not to the formation of secondary crystal phases. For comparison, the XRD pattern of 10 mol % Ba-doped α-TCP reported by Yashima and Kawaike was added. These authors performed a detailed study on the crystal structure and the site preference of the Ba-doped α-TCP through high-resolution synchrotron powder diffraction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…7 The CaO-BaO-P 2 O 5 phase diagram is well understood and includes many complex phases such as (Ca,Ba) 2 P 2 O 7 , Ca 2 Ba(PO 4 ) 2 , (Ca,Ba) 3 (PO 4 ) 2 , Ca 10 (PO 4 ) 6 O and Ca 4 (PO 4 ) 2 O. [8][9][10] However the system has been little explored for phosphor applications in combination with blue LEDs. Lagos reported the behavior of (Ca,Ba) 2 P 2 O 7 :Eu 2+ as a blue phosphor and (Ca,Ba) 3 (PO 4 ) 2 :Eu 2+ as a yellow phosphor for UV excitation, but these are not alternatives to YAG:Ce 3+ since they are poorly matched to blue LEDs.…”
Section: Introductionmentioning
confidence: 99%